Analysis of the characteristics of coronary artery lesions in patients with obstructive sleep apnea-hypopnea syndrome and influencing factors. Issue 4 (1st December 2014) - Sun, Bin; Liu, Jing; Huang, Ding; Liu, Cheng
Abstract : Objective: The current study involved an analysis of the characteristics of coronary artery lesions of patients with obstructive sleep apnea-hypopnea syndrome (OSAHS) and the corresponding influencing factors. Methods: One hundred twenty patients were selected by sleep apnea monitoring and coronary angiography. According to the apnea-hypopnea index (AHI), the patients were divided into the following 3 groups: patients with an AHI<10 times/h as the control group ( n =25); patients with an AHI=100∼15 times/h as the mild OSAHS group ( n =32); and patients with an AHI>15 times/h as the moderate-to-severe OSAHS group ( n =63). The clinical and laboratory test data of patients in each group were collected. A single-factor ANOVA and multi-factor logistic regression analysis were performed on the study data to analyze the coronary artery lesions in patients with OSAHS and the corresponding influencing factors. Results: (1) With respect to smoking, alcohol consumption, BMI, blood glucose, blood lipids, and blood pressure among the three groups, there were no significant differences between the three groups; however, age did differ among the three groups ( P <0.05). (2) The incidence of anterior descending artery, right coronary artery, single-vessel, and coronary artery lesions as determined by coronary angiography was significantly different ( P <0.05). The incidence of these vascular lesions in the moderate-to-severe group was higher than the mild group, and the incidence of coronary artery lesions in the moderate-to-severe group was higher ( P <0.0167). (3) Based on multi-factor logistic regression analysis, alcohol consumption (OR=7.058; 95% CI, 1.953–25.508), age (OR=1.845; 95% CI, 1.121–3.038), and the AHI (OR=2.404; 95% CI, 1.088–5.314) were the major risk factors for coronary artery lesions. Alcohol consumption (OR=12.114; 95% CI, 3.058–47.979) and the AHI (OR=3.052; 95% CI, 1.210–7.694) were the risk factors for single-vessel disease. Age (OR=2.812; 95% CI, 1.236–6.400) was the major risk factor for multi-vessel disease. Conclusion: The probability of coronary artery lesions increased with OSAHS severity. The main manifestation of the increased possibility was single-vessel coronary artery lesions. In single-vessel disease, the anterior descending branch and the right coronary artery were the most vulnerable, which may be related to the anatomic distribution. Alcohol consumption, age, and AHI are the major risk factors for coronary artery lesions. Alcohol consumption and AHI are major risk factors for single-vessel disease. Age is the main risk factor for multi-vessel disease.